Whole-Exome Sequencing Enables the Diagnosis of Variant-Type Xeroderma Pigmentosum - Fang, Xiaokai; Sun, Yonghu (Frontiers in Genetics, 2019)
Background Xeroderma pigmentosum (XP) is a rare autosomal, recessive, inherited disease. XP patients exhibit high sensitivity to sunlight and increased incidence of skin cancer. The different XP subtypes, which are caused by mutations of eight distinct genes, show some specific clinical manifestations. XP variant (XPV) is caused by mutations in the gene encoding DNA polymerase eta (POLH). Case Presentation We report a family that included two XP patients whose parents were first cousins. The proband is a 36-year-old male who developed a large number of pigmented freckle-like lesions starting at 4 years of age; later, he displayed typical psoriasis manifestation, abnormal renal function and hyperglycaemia. He was suspected as suffering from dyschromatosis symmetrica hereditaria (DSH), but negative results were obtained in candidate gene analyses. Whole-exome sequencing was performed in four subjects, including the two patients and two controls, and a new pathogenic homozygous nonsense mutation (c.353dupA, p. Y118_V119delinsX) of the POLH gene, which was identified in all nine family members by Sanger sequencing, was detected in the patients. Conclusion A novel XPV pathogenic homozygous nonsense mutation in the POLH gene was identified. Our case proves that next-generation sequencing is an effective method for the rapid diagnosis and determination of XP genetic etiology.